2019
DOI: 10.5093/ejpalc2020a1
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles and Aggressive Adolescents: Relationships with Self-esteem and Personal Maladjustment

Abstract: A B S T R A C TCurrent emergent studies are seriously questioning if parental strictness contributes to adolescent adjustment. This study examined whether the relationship between authoritative (warmth and strictness), authoritarian (strictness without warmth), indulgent (warmth without strictness), and neglectful (neither warmth nor strictness) parenting styles shows equal or different pattern of adjustment and maladjustment for aggressive and non-aggressive adolescents. The sample consisted of 969 Spanish ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
69
3
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 76 publications
(90 reference statements)
12
69
3
11
Order By: Relevance
“…It is argued that, in these horizontal collectivist cultures, parental imposition and strictness might be negatively perceived by children. The results of the study are in line with some previous studies that have shown that the indulgent style (i.e., warmth without strictness) provides important benefits in terms of psychosocial adjustment for adolescents, including greater school adjustment [106] and optimal learning strategies [97], psychosocial development [95] or environmental empathy and connectedness with nature [84], and protection against alcohol use and abuse [61], marijuana and tobacco [95], personal maladjustment [65] or traditional bullying and cyberbullying victimization [27].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is argued that, in these horizontal collectivist cultures, parental imposition and strictness might be negatively perceived by children. The results of the study are in line with some previous studies that have shown that the indulgent style (i.e., warmth without strictness) provides important benefits in terms of psychosocial adjustment for adolescents, including greater school adjustment [106] and optimal learning strategies [97], psychosocial development [95] or environmental empathy and connectedness with nature [84], and protection against alcohol use and abuse [61], marijuana and tobacco [95], personal maladjustment [65] or traditional bullying and cyberbullying victimization [27].…”
Section: Discussionsupporting
confidence: 89%
“…The minimum sample size required for conventional statistical errors type I, α = 0.05, and type II, β = 0.05, was calculated with a priori power analysis [63,64], it was fixed at a medium-small effect size (f = 0.17, estimated from ANOVAs (Analysis of Variance) by Lamborn et al, 1991 [41]) in an univariate F-test between the four parenting style groups [27,65]. A priori power analyses (α = 0.05, 1 -β = 0.95, and f = 0.17) showed a minimum sample size of 600 participants [35,51].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the findings regarding adolescents' emotional states (e.g. a sense of being difficult to cope with) and the interplay with CPV, support previous evidence of CPV research (Ibabe et al, 2014a(Ibabe et al, , 2014bMartinez-Ferrer et al, 2018) as well as wider family research with both community samples (Perez-Gramaje, Garcia, Reyes, Serra, & Garcia, 2020;Garcia, Lopez-Fernandez, & Serra, 2018) and legal samples (Steinberg, Blatt-Eisengart & Cauffman, 2006). Poor psychosocial competence and maladjustment was found as well as hyperactivity, low impulse control and difficulties with interpersonal relationships.…”
Section: Implications and Future Researchsupporting
confidence: 83%
“…In addition, some studies that examined parenting styles in European and Latin American countries found that indulgent parenting (warmth but not strictness) was related to optimal child development. Indulgent parenting (also labelled as permissive, characterized by warmth but not strictness) was related to equal or even better psychosocial adjustment than authoritative parenting, whereas authoritarian parenting (strictness but not warmth) and neglectful parenting (neither warmth nor strictness) have consistently been related to the worst psychosocial adjustment [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%